Normal Penetration of the Rigid Penetrator Into Elastic-Plastic Half-Space With Viscosity - WŁODARCZYK, E. (Engineering Transactions, 2007)
The analytical closed-form solution of the normal penetration problem of a rigid core (penetrator) of a jacket-bullet into elastic-plastic half-space (thick target) is presented in this paper. The cohesive resistance of the target, frictional effects, and acceleration of the target material in the neghbourhood of the penetrator (virtual mass effect) is taken into consideration. On the basis of the derived closed analytical formulae, influence of these parameters on the penetration depth may be investigated. Among other things, it appears from calculations that the boundary penetration depth is intensivly reduced by the force of viscous friction. Moreover, the mean value of the coefficient of viscous friction (¹) for a given penetratortarget system may be determined. For this purpose it is necessary to define experimentally the penetration depth hk at a given impact velocity.